Toxicity of Glufosinate-Ammonium Herbicide in Giant Freshwater Prawn (𝙈𝙖𝙘𝙧𝙗𝙧𝙖𝙘𝙝𝙞𝙪𝙢 𝙧𝙤𝙨𝙚𝙣𝙗𝙚𝙧𝙜𝙞𝙞) - Wongchan, Butsayamat; Rakkaew, Kaltima; Jandee, Nantakarn; Kiatprasert , Pongpat; Kumla, Sugunya; Thanomsit, Chutima (Burapha Science Journal, 2025)
Background and Objectives : Nowadays, the Thailand export agricultural product was intensively expanded. Therefore, Thailand agricultural sector expels the promotion in chemical using trends in agricultural system. By these economic forces, farmers have encountered large-scale farming production sufficiently for increase consumer demands such agrochemicals using such as chemical fertilizers and herbicides is an important factor for farmers relying on. Herbicides are widely used not only to increase crop yields but also to control weed growth and dissipation that hinders nutrient needs for crop. So far, high volume of herbicide imports value is an evidence reflecting the remains agrochemicals farming system in contribution to the environmental pollution and crisis via inappropriate and excessive usage. Thereby the improper chemicals practice and usage arising from overuse or runoff into nearby ecosystems leads to the herbicide accumulation in environments such as soil, water, and even the air that causes the long-term contamination. Aquatic animals Inevitably affects to this risk by exposure to herbicide–contaminated environments. Aquatic animal health is damaged by herbicide effect in either immediate toxicity or long-term accumulation in animal tissue. Although the concentration of herbicides detected in aquatic animals remains in safety range for consuming, the long-period exposure of such chemicals bring into health risk, especially the human diet made from these aquatic animals. Glufosinate ammonium is herbicide disrupting cell structure and function of plants, but has no effect in aquatic invertebrates. This study aimed to investigate the short-term toxicological effects of glufosinate ammonium on the giant freshwater prawn (Macrobrachium rosenbergii), a commercially and ecologically important species in Thailand. However, limited data about the response to its glufosinate ammonium exposure in this species was little studied. Therefore, the objective of this research is to examine the physiological and biochemical effects of this herbicide on M. rosenbergii. The changes in tissues and blood cells were observed including characterizing the acetylcholinesterase (AChE) expression using the Western blot technique in the nervous system. This key enzyme acts as a valuable biomarker for neurotoxicity in aquatic organisms. Thereby determining the alteration in both cellular and molecular responses, this study provides better understanding pathophysiological effect on post-exposure herbicides of aquatic animals in contribution to threatening human health risk via the contaminated food consuming. Methodology : Glufosinate ammonium toxicity was assessed in this study for determining its effect on cumulative mortality rate in relation to acetylcholinesterase (AChE) expression as well as the physiological response after glufosinate ammonium exposure was investigated by measuring the total hemocytes and histopathological alteration in muscular and intestinal tissue. After glufosinate ammonium exposure to healthy giant freshwater prawns at effective concentrations from 0 (control), 250, 300, 350, 400, and 450 µL/L, respectively. For simulating possible duration time and exposure levels in nature this experimented duration time were performed at 24, 48, 72, and 96 hours.Moreover, the responsive biochemical function in protein expression profile and AChE expression by using western blot analysis was determined for neurotoxic damage AChE acting as a biomarker. Main Results : The study for glufosinate ammonium toxicity revealed an increased mortality of post-exposure of M. rosenbergii in time and concentration dependent manner that evidenced on the increased cumulative mortality.Western blot analysis demonstrated the significantly decrease in AChE expression while increased exposure time. AChE was detected at molecular weight of approximately 71 kilodaltons (kDa) in hemolymph. The awkwardly decreased in AChE expression in glufosinate ammonium-exposed prawns revealed its neuronal disruptive effect on neuromuscular function. For histopathological examination, the exposed prawns displayed the structural damage of hemocytes in multiple cell types, including large granular hemocytes (LGH), small granular hemocytes (SGH), and hyaline-type cells (H-type). Evidence on irregular cell boundaries, disrupted cell membranes and cytoplasmic disintegration suggested the herbicide effect on to the immunity compromises. For histological study, swelling and degeneration of muscular tissue was shown, thereby its direct effect on muscle structure and function. Similarly, after exposure pathological changes was shown in prawn intestinal tissues such as lumen dilation and fusion of microvilli, thereby reducing nutrient absorption and hindering digestion efficiency. Therefore, much longer exposure time with an effective concentration of glufosinate-ammonium, the growth and health was retarded by the persistent changes at vital structure of the exposed prawns. Conclusions : The health burden of giant freshwater prawns (Macrobrachium rosenbergii) is caused by the toxic effect of glufosinate ammonium exposure, leading to a high morbidity rate in a concentration- and time exposure-dependent manner. At a high dose and with increased time of exposure, glufosinate ammonium exerted its effect by causing a decline in AChE activity in relation to decreased acetylcholinesterase (AChE) expression. At the biochemical and histological levels in glufosinate ammonium–exposed prawns, hemocyte morphological abnormalities and tissue structural damage caused by disturbed AChE activity were observed. From these results, AChE is determined as a sensitive biomarker for effectively patrolling herbicide contamination in aquatic ecosystems.